GREEN ACCOUNTING BERBASIS MASLAHAH DALAM UPAYA MENUNJANG KEBERLANGSUNGAN USAHA ENTITAS BISNIS - Masyhuri Masyhuri (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This study aims to understand the concept of maslahah-based green accounting to support business continuity (going concern) business entities in the environmental field. This study uses qualitative research with a phenomenological approach to understand the implementation of green accounting through the concept of maslahah to support the going concern of a business entity. Data were obtained through references from the Qur'an, journals, articles, and books related to green accounting. Based on the discussion conducted, it is known that the application of green accounting has a positive impact on efforts to prevent environmental pollution. The application of maslahah-based green accounting is conceptualized in environmental care, involvement in the environment, environmental reporting, and environmental audits based on maslahah. In addition, the application of maslahah-based green accounting through the internalization of religion, soul, mind, lineage, and property will ensure the existence and business continuity (going concern) of more useful business entities.